BIOECOLOGICAL STATUS OF THE TURKESTAN FUMIGATUS (FUMARIOLA TURKESTANICA KORSH.) GROWING IN THE SHAHIMARDON REGION (Scientific journal of the Fergana State University, 2026)
This article analyzes the bioecological characteristics, distribution area, population, adaptation to the natural environment, and threats of the Turkestan fumarole (Fumariola turkestanica Korsh.), a rare and endemic plant growing in the Shahimardon region of Fergana region. The article presents analytical results based on literature analysis and field observations over the years, and provides recommendations for the development of conservation measures.